Possibilities of Magnetic Resonance and Computed Tomography in Early Detection of Joint Changes In Rheumatoid Arthritis Disease (Texas Journal of Medical Science, 2023)
Early detection of joint damage by MRI and CT methods relative to the stage of the disease in patients with rheumatoid arthritis observed